Linguistic Description Of The Lexical Level And Its Learning Status - Begimova Gulshoda Jahon kizi (International Journal on Integrated Education, 2023)
Language is created by society, and its fate is closely related to the fate of society. Language is a social phenomenon. As a social phenomenon, it is distinguished from natural phenomena. For example, natural-biological and physiological characteristics of people (eating, breathing, development, etc.) develop in accordance with the laws of nature, independently of society. But in order to speak and think in a language, there must be a community of people. Therefore, unlike natural phenomena, language is a social phenomenon created and served by human society.